The Rebirth of Bourbon Building a Tourism Economy in Small-Town, USA. - Coomes, Steve (Economics of Vice Ser., 2020)
With the popularity of bourbon becoming a global phenomenon, the historic town of Bardstown, KY, is booming - but all booms come with growing pains. This first book of the new Economics of Vice series tells the story of Bardstown's challenges, traditions, opportunities, and the people who shouldered them all.